Market Reaction to Actual Share Repurchase in Malaysia - Isa, Mansor; Ghani, Zaidi; Lee, Siewâ€Peng (Asian Journal of Business and Accounting, 2017)
This paper examines share price reaction surrounding actual share repurchases made by Malaysian listed firms from 2001 until 2005. Using event study methodology and the market model, the evidence indicates that a significant increase in share prices occurs in a threeday period beginning from the repurchase day. We also find evidence that there is a general price decline in the preâ€purchase period that suggests that firms made their repurchase after a period of consecutive price declines. This evidence clearly indicates the existence of a signalling effect and is consistent with the undervaluation hypothesis. It also indicates that the share repurchase programme can be used as an effective tool for price stabilisation. Keywords: Open Market Repurchase, Signalling Hypothesis, Share Repurchase